2017
DOI: 10.1113/ep086400
|View full text |Cite
|
Sign up to set email alerts
|

Maternal voluntary physical activity attenuates delayed neurodevelopment in malnourished rats

Abstract: What is the central question of this study? In the present study, a reproducible model of maternal voluntary physical activity was developed to evaluate the adaptive response of physical activity by attenuating the effects of maternal undernutrition on physical features, reflex ontogeny and growth trajectory of offspring during development. What is the main finding and its importance? Maternal physical activity may induce neuronal maturation of sensorimotor connections impacting on the patterns of locomotor ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 41 publications
1
22
1
Order By: Relevance
“…In one follow-on observation, for example, Herring and colleagues 339 reported that exercise in the pregnant mother slows the development of the Aβ plaque pathology of her progeny, suggesting epigenetic transmission of the effect for at least one generation (and another challenge for human mothers determined to have the perfect baby). Fragoso and colleagues 340 provided a confirming observation that maternal exercise during pregnancy in rats attenuates the damage to the fetal brain caused by malnutrition.…”
Section: Lack Of Oxygen: Ischemia Remote Ischemia Exercise-induced mentioning
confidence: 92%
“…In one follow-on observation, for example, Herring and colleagues 339 reported that exercise in the pregnant mother slows the development of the Aβ plaque pathology of her progeny, suggesting epigenetic transmission of the effect for at least one generation (and another challenge for human mothers determined to have the perfect baby). Fragoso and colleagues 340 provided a confirming observation that maternal exercise during pregnancy in rats attenuates the damage to the fetal brain caused by malnutrition.…”
Section: Lack Of Oxygen: Ischemia Remote Ischemia Exercise-induced mentioning
confidence: 92%
“…This categorisation is aligned with previous studies. 25,26 Earlier literature has also shown that such behavioural traits, i.e. the propensity or not for spontaneous physical activity, can be regulated by central (mRNA expression in the central nervous system) and/or peripheral (mRNA expression in skeletal muscle) mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…These parameters were used to classify the rats according to their level of daily physical activity: inactive (I, n = 6), active (A, n = 4) or very active (VA, n = 5) according to previous studies. 25,26 After mating, rats continued to have access to the running wheel during gestation ( Fig. 1).…”
Section: Voluntary Physical Activity Measurementsmentioning
confidence: 99%
See 2 more Smart Citations